The Effect of Teacher Performance on Learning Outcomes of Grade VI Students of State Elementary School 070979 Sifalaete Gunungsitoli City - Gulo, Ratna Susanti; Zega, Yamolala; Mendrofa, Syah Abadi; Telaumbanua, Eliagus (ProBisnis : Jurnal Manajemen, 2025)
This study aims to determine the effect of teacher performance on the learning outcomes of sixth-grade students at SDN 070979 Sifalaete, Gunungsitoli City. The research method used is a quantitative method. Data were collected through teacher performance questionnaires and student learning outcomes questionnaires along with field documentation. Data analysis used simple linear regression. The results showed that teacher performance had a positive and significant effect on student learning outcomes, with a coefficient of determination (R²) of 74.4%, which means that teacher performance contributed 74.4% to changes in student learning outcomes, while the rest was influenced by other factors. Thus, the better the teacher performance, the higher the student learning outcomes.